Climate-Smart Agriculture and Food Security: A Bibliometric Analysis - Loso Judijanto (West Science Interdisciplinary Studies, 2025)
Climate change poses significant challenges to agricultural productivity and global food security, particularly in regions highly dependent on climate-sensitive farming systems. Climate-Smart Agriculture (CSA) has emerged as an integrated approach aimed at enhancing agricultural productivity, strengthening resilience to climate variability, and reducing greenhouse gas emissions. Despite the rapid growth of CSA-related studies, a comprehensive understanding of the global research landscape, thematic evolution, and collaboration patterns remains limited. This study aims to map and analyze the scientific development of CSA and food security research through a bibliometric approach. Using publication data indexed in the Scopus database, this study applies network and visualization analysis with VOSviewer to examine keyword co-occurrence, citation structures, co-authorship networks, and geographical research distribution. The findings reveal that research on CSA and food security has expanded significantly, with dominant themes focusing on climate change adaptation and mitigation, smallholder farming systems, crop resilience, sustainable land management, and technology adoption. The results also highlight strong international collaboration networks, particularly among countries in Asia, Europe, and Africa, reflecting the global relevance of CSA in addressing food security challenges. This study contributes to the literature by providing a systematic overview of research trends, influential works, and emerging themes, offering valuable insights for researchers, policymakers, and practitioners in designing evidence-based strategies for sustainable agriculture and food security under climate change.